PENGELOLAAN SDM UMKM BERBASIS DIGITAL DI PANDEMI COVID-19 - Tri Handayani; Galuh Aditya (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
The current Covid-19 pandemic has changed the state of the economy in Indonesia as well as changes in the economy with the collapse of the macro and micro economic sectors. MSMEs as one of the drivers of the economy in Indonesia are also greatly affected by the COVID-19 pandemic. The public's purchasing power for products produced by MSMEs is low during the pandemic so that business operators must be creative in order to remain accepted by consumers. With a descriptive approach research method data obtained through online document searches and literature review. The results of the study are the use of social media in the form of product advertisements, and the use of people/artists/public figures can be used by MSMEs youtube, instagram and facebook with interesting content, straightforward in exploration as a means of introducing, promoting products and can increase the level of purchasing power in selling products. produced by SMEs.Keywords: MSMEs, Marketing Strategy, Purchasing Power, Social Media